Suppression of Interleukin-33 Bioactivity through Proteolysis by Apoptotic Caspases - LAVELLE, EDWARD; MARTIN, SEAMUS JOSEPH; LUTHI, ALEXANDER; SHERIDAN, CLARE (My University, 2009)
Interleukin-33 (IL-33) is a member of the IL-1 family and is involved in polarization of T cells toward a T helper 2 (Th2) cell phenotype. IL-33 is thought to be activated via caspase-1-dependent proteolysis, similar to the proinflammatory cytokines IL-1? and IL-18, but this remains unproven. Here we showed that IL-33 was processed by caspases activated during apoptosis (caspase-3 and -7) but was not a physiological substrate for caspases associated with inflammation (caspase-1, -4, and -5). Furthermore, caspase-dependent processing of IL-33 was not required for ST2 receptor binding or ST2-dependent activation of the NF-?B transcription factor. Indeed, caspase-dependent proteolysis of IL-33 dramatically attenuated IL-33 bioactivity in vitro and in vivo. These data suggest that IL-33 does not require proteolysis for activation, but rather, that IL-33 bioactivity is diminished through caspase-dependent proteolysis within apoptotic cells. Thus, caspase-mediated proteolysis acts as a switch to dampen the proinflammatory properties of IL-33.
IN_PRESS
[PMID: 19559631 ]
Keywords: MOLIMMUNO; CELLIMMUNO